First report of aphaenopsoid trechines (Coleoptera: Carabidae: Trechini) from Serbia, with descriptions of new taxa - Ćurčić, Srećko; Pavićević, Dragan; Vesović, Nikola; Marković, Đorđe; Petković, Matija; Bosco, Fabrizio; Kuraica, Miloš; Nešić, Dragan (Zootaxa, 2018)
The trechine ground beetle taxa, Velesaphaenops gen. n., Velesaphaenops tarensis sp. n., and Acheroniotes lethensis sp. n., are described and diagnosed. The new taxa differ clearly from their closest relatives in a number of external characters and the shape of the genitalia. They probably belong to phyletic lineages of Pliocene age (the age of the palaeokarst of Kamena Gora and Mt. Tara). The new taxa are endemic to western and southwestern Serbia. Keys to the aphaenopsoid trechine genera in Serbia and to species of the genus Acheroniotes Lohaj & Lakota, 2010 are appended.